Implementation of Nursing Care During Covid-19 Pandemic in Outpatient Installation of Hospital - Eka Yuliani; Armen Patria (Indonesian Journal of Global Health Research, 2022)
Nursing care must follow a new lifestyle during Covid-19 pandemic, called the new normal. Nursing care during the pandemic in outpatient installations feels somewhat reduced. The purpose of this study was to analyze the factors that influence the implementation of nursing care during Covid-19 pandemic in the outpatient installation of hospital. The research method used is descriptive correlation design with a cross-sectional approach. The population used is nurses and patients in outpatient hospitals. Total sampling technique is involving 46 nurses and 46 patients. Each research subject is only observed once and measurements are made on the status of the character or subject variable at the same time. The results showed that there was a relationship between nurses' age, nurses' perceptions of the management tools in the form of money and materials and machines on the implementation of nursing care perceived by patients. Implication: if nursing care is not optimal, if it continues, it will result in a decrease in the quality of health services.